Phase II study of irinotecan plus doxorubicin for early recurrent or platinum-refractory ovarian cancer: interim analysis. Issue 1 (1st January 2007) - Nishimura, S.; Tsuda, H.; Hashiguchi, Y.; Kokawa, K.; Nishimura, R.; Ishiko, O.; Kamiura, S.; Hasegawa, K.; Umesaki, N.
Abstract : The aim of this study was to evaluate the efficacy and toxicity of irinotecan and doxorubicin in the treatment of patients with early recurrent or platinum-refractory ovarian cancer. Nineteen woman from five different institutions were treated. Two patients had platinum-refractory cancer, 11 had platinum-resistant disease, and 6 had platinum-sensitive tumors. An intravenous infusion of Irinotecan (50mg/m 2 ) was given on days 1, 8, and 15, while doxorubicin (40mg/m 2 ) was administered as an intravenous bolus on day 3. This treatment schedule was repeated every 4 weeks. Among the 13 patients defined as having platinum-refractory/platinum-resistant disease, 4 patients achieved a clinical response (30.8%, 95% CI: 9.1–61.4), while only one of 6 patients defined as having platinum-sensitive disease achieved a clinical response (16.7%, 95% CI: 0.4–64.1). Leukopenia and neutropenia were the major dose- limiting toxicities. Grade 3 or 4 leukopenia and neutropenia were noted in 24 (48%) and 33 (66%) of the courses, while febrile neutropenia occurred in 2 courses. Five patients (26%) had grade 2 or worse diarrhea during 7 courses. Our data demonstrated that this regimen might be comparable to standard approved agents in patients with early recurrent or platinum refractory ovarian cancer.